1995
DOI: 10.1007/bf00198316
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the use of antibacterial drugs in the countries of central and eastern Europe

Abstract: Use of systemic antibacterial drugs in the countries of central and eastern Europe (CCEE) has been studied using the defined daily doses (DDD) methodology. For the comparison, national wholesale data from Bulgaria, the Czech Republic, Estonia, Hungary, Lithuania, Slovakia, Slovenia and Romania for the years 1989 and 1992 were used, i.e. for the years before and after the rapid sociopolitical changes in these countries. Substantial differences in the patterns of antibacterial drug use between countries as geogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…Previous studies on drug use have shown that the use of antibiotic drugs varies quantitatively and qualitatively between countries. 9,10 Previous studies have shown that antibacterial resistance is not a major problem in Sweden. 5,15,20 Data on antibiotic deliveries from the pharmacy have been collected for several years but have hitherto not been analyzed in relation to resistance data.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on drug use have shown that the use of antibiotic drugs varies quantitatively and qualitatively between countries. 9,10 Previous studies have shown that antibacterial resistance is not a major problem in Sweden. 5,15,20 Data on antibiotic deliveries from the pharmacy have been collected for several years but have hitherto not been analyzed in relation to resistance data.…”
Section: Introductionmentioning
confidence: 99%
“…Проблемою є надмірне використання анти-біотиків при нетяжких інфекціях, їх нераціональне використання внаслідок відсутності доступу до ква-ліфікованої медичної допомоги або нестачі у паці-єнта грошей для проходження повного курсу терапії [17]. За даними Центру з контролю і профілактики захворювань США, до половини призначень анти-біотикотерапії в амбулаторних умовах є необґрунто-ваним [18]. На жаль, на сьогодні в Україні діє лише один нормативний документ, присвячений системі інфекційного контролю, -це Наказ МОЗ Украї-ни № 234 від 10.05.2007 «Інструкція з організації та впровадження системи інфекційного контролю в акушерсько стаціонарах», який вводить поняття системи інфекційного контролю, регламентує клі-нічний, мікробіологічний та епідеміологічний моні-торинг за внутрішньолікарняними інфекціями.…”
Section: оригінальні дослідження / Original Researchesunclassified